Social Cognition in Children Born Preterm: A Perspective on Future Research Directions - Zmyj, Norbert; Witt, Sarah; Weitkämper, Almut; Neumann, Helmut; Lücke, Thomas (Frontiers in Psychology, 2017)
Preterm birth is a major risk factor for children’s development. It affects children´s cognitive and intellectual development and is related to impairments in IQ, executive functions, and well-being, with these problems persisting into adulthood. While preterm children’s intellectual and cognitive development has been studied in detail, their social development and social-cognitive competencies have received less attention. Namely, preterm children show problems in interactions with others. These interaction problems are present in relationships with parents, teachers, and peers. Parents’ behavior has been identified as a possible mediator of children’s social behavior. Maternal sensitivity and responsiveness as well as absence of mental disorders foster children’s social development. In this article, we will report on the social side of impairments that preterm children face. The review of the literature revealed that preterm infants’ joint attention abilities are impaired: They are less likely to initiate joint attention with others and to respond to others’ efforts to engage in joint attention. These deficits in joint attention might contribute to later impairments in social cognition, which in turn might affect social interaction skills. Based on these three domains (i.e., problems in social interaction, parental behavior, and impairments in joint attention), we suggest that preterm children’s social cognitive abilities should be investigated more intensively.